Comparison of Pre Pregnancy BMI and Trimester Specific Weight Gain on Fetomaternal Outcome - Shah Gul Khan, Aalia Yousaf, Mahin Saeed, Ayisha Raja, Ammara Naz, Hooria Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Pregnancy BMI and trimester-specific weight increase are two indicators of maternal weight, which is important in determining the health outcomes for both the mother and the fetus. Objective: This study aim was to compare the effects of pre-pregnancy BMI and trimester-specific weight gain on fetomaternal outcomes, providing a more comprehensive understanding of their combined impact on maternal and neonatal health. Methodology: A prospective observational study was conducted at Combined Military Hospital, Malir Cantonment, from April to December 2023. Using certain inclusion and exclusion criteria, 135 pregnant women with singleton pregnancies were included. Antenatal data was used to gather maternal characteristics, such as pre-pregnancy BMI, weight increase by trimester, and obstetric history. At delivery, fetomaternal outcomes were recorded. SPSS version 26 was used for the statistical analysis, and the chi-square and t-tests were used for the continuous and categorical variables, respectively. Results: The research included 135 pregnant women with a total gestational weight increase of 10.1 ± 3.2 kg and a mean pre-pregnancy BMI of 24.8 ± 3.9 kg/m². Overweight (40%) and obese (44.44%) women had substantially higher cesarean section rates than normal-weight (23.61%) and underweight (20%) women (p = 0.021). Compared to normal-weight (8.33%) and overweight (13.33%) groups, underweight (26.67%) and obese (22.22%) groups had higher rates of preterm birth (p = 0.045). Macrosomia (>4.0 kg) was more common in overweight (13.33%) and obese (11.11%) women (p = 0.027), while low birth weight (<2.5 kg) was most common in underweight women (40%) (p = 0.032). Overweight women had the highest prevalence of gestational hypertension (20%) (p = 0.018). Neonatal outcomes were strongly impacted by trimester-specific weight increase, with macrosomia (p = 0.031) being related with excessive weight growth and low birth weight (p = 0.012) with insufficient weight gain. Conclusion: Pre-pregnancy BMI and trimester-specific weight gain significantly influence fetomaternal outcomes, emphasizing the importance of optimal weight management during pregnancy to reduce adverse complications. Keywords: Pre-pregnancy BMI, trimester-specific weight gain, fetomaternal outcomes, cesarean section, preterm birth, gestational hypertension.